Z2 quantum memory implemented on circuit quantum electrodynamics - Kwek, Leong Chuan (2015)
We present a technique to store and retrieve single- and two-qubit states into a parity-protected quantum memory implemented on a state-of-the-art superconducting circuit architecture. Our proposal relies upon a specific superconducting circuit design that permits a tunable qubit-resonator coupling strength. The latter allows us to adiabatically tune from the weak coupling to the ultrastrong coupling regime of light-matter interaction, where a controllable and well-protected effective two-level system is defined due to the Z2 parity symmetry. Storage and retrieval time of the qubit are in a few nanoseconds timescale, which is far below the effective qubit coherence time.